(untitled) (Indonesian Theological Justice Review, 2025)
Indonesia’s urban poor face significant challenges, including inadequate housing, limited access to healthcare, and low-quality education. This paper explores the role of theology in addressing the social, economic, and political marginalization of the urban poor in Indonesia. Drawing from Islamic, Christian, and indigenous theological teachings on justice and compassion, the study examines how religious communities have responded to the plight of the urban poor through advocacy, charity, and social programs. The research focuses on how theology motivates religious communities to address systemic inequalities and provide support for marginalized groups, emphasizing the importance of justice, dignity, and empowerment. The paper also evaluates the role of faith-based NGOs and religious leaders in advocating for policies that improve the living conditions of the urban poor, examining case studies of religious interventions in urban slums. The study argues that theological ethics provides a foundation for addressing the root causes of poverty and for creating more equitable systems. It recommends fostering partnerships between religious organizations, government agencies, and NGOs to implement justice-driven urban policies and to empower marginalized communities.